2009
DOI: 10.1002/ijc.24412
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of lipid peroxidation‐derived DNA lesions in iron‐overloaded thalassemic mouse livers: Comparison with levels in the lymphocytes of thalassemia patients

Abstract: In thalassemia patients, iron overload can stimulate lipid peroxidation (LPO), thereby generating miscoding DNA adducts. Adducted DNA was measured in the lymphocytes of b-Thal/Hb E patients and healthy controls and in the organs of thalassemic mice. edA, edC and M 1 dG residues were quantified by 32 P-postlabeling-TLC/ HPLC. M 1 dG levels in lymphocyte DNA from patients were 4 times as high as in controls, while the increase in edA and edC was not significant. Adducted DNA accumulated in the liver of thalassem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Remarkably, many bacteria also have oxidation-sensing mechanisms to respond to and counteract the oxidation-mediated host response [34]. Our results also showed that lipid peroxidation increased markedly in some Kp-infected organs of lyn −/− mice as compared with those of WT mice [19]. …”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Remarkably, many bacteria also have oxidation-sensing mechanisms to respond to and counteract the oxidation-mediated host response [34]. Our results also showed that lipid peroxidation increased markedly in some Kp-infected organs of lyn −/− mice as compared with those of WT mice [19]. …”
Section: Discussionmentioning
confidence: 54%
“…Increased MPO in these major organs suggests that oxidative stress may have resulted from systemic spread of the invading Kp bacteria. As increased oxidation can also cause tissue injury by oxidative degraded lipids, we used a thiobarbituric acid-reactive substrate assay to detect lipid peroxidation in the lung, liver, spleen, and kidney tissue [19]. To our no surprise, lipid peroxidation significantly increased in the organs of lyn −/− mice compared with that of WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the direct correlation between iron status parameters and MDA or total carbonyl is not well examined; in the present study, this correlation was statistically analyzed. However, some researches mentioned that excess iron concentration can stimulate lipid peroxidation (27) which is a well-defined mechanism of cellular damage in animals. Increased levels of erythrocyte free reactive iron and lipid peroxidation end product are associated with low erythrocyte glutathione level.…”
Section: Resultsmentioning
confidence: 99%
“…(27) However, studies have indicated that no direct association between serum iron parameters and MDA and total carbonyl concentrations is indicated. In one study, the strongest predictor of increased MDA in patients with thalassemia is liver iron concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Al-Hakeim et al reported no statistically significant correlation between iron status parameters and MDA or total carbonyl in patients with β-thalassemia major 22 . Excessive iron concentrations can stimulate lipid peroxidation in thalassemia mouse models, which resemble thalassemia patients receiving blood transfusions, 23 however these studies have indicated no direct association between serum iron parameters and MDA 22, 23. Instead, the strongest predictor of increased MDA in patients with severe thalassemia would be the liver iron concentration 24 …”
Section: Discussionmentioning
confidence: 99%